THE EFFECTIVENESS OF POSITIVE MENTAL HEALTH PROGRAM FOR GENDER DIVERSE UNDERGRADUATE STUDENTS IN PUBLIC UNIVERSITIES, BANGKOK THAILAND - POEDLOKNIMIT, CHUNIPHA; ตันติวิวัทน์ สุดารัตน์; สิริอัตตะกุล ปริญญา (Thai Interdisciplinary and Sustainability Review, 2024)
This research aimed to develop and evaluate the effectiveness of a positive mental health program for gender diverse undergraduate students in public universities in Bangkok, Thailand, using a quasi-experimental research design. The sample consisted of 40 gender diverse undergraduate students, divided into an experimental group (n = 20) and a control group (n = 20). The study employed a pretest-posttest control group design with a 6-week follow-up. Data were analyzed using descriptive statistics and hypotheses were tested using independent sample t-tests and one-way repeated ANOVA. The results revealed that, after the intervention, the experimental group had significantly higher mean scores of positive mental health than the control group at the .01 level, both overall and in all components. Additionally, when comparing the positive mental health scores of the experimental group at pre-test, post-test, and follow-up, significant differences were found at the .05 level, with post-test and follow-up scores being higher than pre-test scores. These findings demonstrate the sustained effectiveness of the program in promoting positive mental health among gender diverse undergraduate students.